Longterm alley cropping with four hedgerow species on an Alfisol in southwestern Nigeria effect on crop performance, soil chemical properties and nematode population - Kang, B.T.; Caveness, F.E.; Tian, G.; Kolawole, G.O. (1999)
A longterm alley cropping trial was undertaken on an eroded Oxic paleustalf in the forest-savanna transition zone of southwestern Nigeria from 1981–1993. Two nitrogen fixing hedgerow species (Gliricidia sepium and Leucaena leucocephala) and two non legume hedgerow species (Alchornea cordifolia and Dactyladenia barteri) were used in the trial compared to a control (with no hedgerow) treatment. Plots were sequentially cropped with maize (main season) followed by cowpea (minor season). With 4 m interhedgerow spacing and pruning at 0.75 m height, the mean annual pruning biomass yields were observed in the following order: Leucaena (7.1 t ha−1 ) > Gliricidia (4.9 t ha−1 ) > Alchornea (3.7 t ha−1) > Dactyladenia (3.0 t ha−1 ). Alley cropping with the four woody species greatly enhanced the total plot (woody species + crop) biomass yield/ha as follows; Leucaena (21.8 t ha−1) > Gliricidia (17.7 t ha−1) > Alchornea (11.7 t ha−1) > Dactyladenia (9.5 t ha−1). Total biomass yield of crops in control plot was 5.3 t ha−1. Higher biomass yields with alley cropping also increased nutrient yield and cycling. Gliricidia and Leucaena showed higher nutrient yields than Alchornea and Dactyladenia. Alley cropping with Gliricidia and Leucaena could sustain maize yield at moderate level (>2 t ha−1), which would require a N-rate of 45 kg N ha−1 with sole cropping. Application of N in Gliricidia and Leucaena alley cropping still improved maize yield. Higher nitrogen rates are required for alley cropping with Alchornea and Dactyladenia hedgerows. A low rate of phosphorus application is needed for sustaining crop yields with all treatments. Occasional tillage is recommended to increase maize yield. Alley cropping and tillage showed little effect on cowpea seed yield. Surface soil properties declined with time with continuous cultivation. Alley cropping with woody species maintained higher soil organic carbon, phosphorus and potassium levels. Plots alley cropped with Gliricidia and Leucaena showed lower pH and extractable calcium level. Leucaena alley cropped plot also showed lower magnesium level. The decline in soil pH and extractable cations may be due to increased cation leaching with application of high rates of Gliricidia and Leucaena prunings. Alley cropping with the four woody species showed no effect on population of parasitic nematodes.